The Dynamic Process of Being (a Person): Two Process-Ontological Theories of Personal Identity - Siakel, Daniel R. (Process studies, 2014)
The purpose of this article is to introduce, interpret, and develop two incompatible process-ontological theories of personal identity that have received little attention in analytic metaphysics. The first theory derives from the notion of personal identity proposed in Alfred North Whitehead’s philosophy, but I interpret this notion differently from previous commentators. The Whiteheadian theory may appeal to those who believe that personal identity involves an entity or entities that are essentially dynamic, but has nothing to do with diachronic objectual identity: the (putative) binary equivalence relation that every entity bears to itself, and only to itself even after undergoing intrinsic change. The Whiteheadian theory may also find favor with those who, like Whitehead, reject the possibility of pure processes and hold that in every becoming, something—which need not be an object, thing, or individual substance—becomes. The second theory derives from the notion of recurrent dynamics presented in Johanna Seibt’s General Process Theory. The Seibtian theory may appeal to those who believe that personal identity involves not only an entity or entities that are essentially dynamic, but also the relation of diachronic objectual identity. The Seibtian theory may also find favor with those who, like Broad and Sellars, find reason to postulate pure processes.